2013
DOI: 10.1016/j.joca.2013.05.015
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental pain sensitivity differs as a function of clinical pain severity in symptomatic knee osteoarthritis

Abstract: Objective Pain in knee osteoarthritis (OA) has historically been attributed to peripheral pathophysiology; however, the poor correspondence between objective measures of disease severity and clinical symptoms suggests that non-local factors, such as altered central processing of painful stimuli, also contribute to clinical pain in knee OA. Consistent with this notion, recent evidence demonstrates that patients with knee OA exhibit increased sensitivity to painful stimuli at body sites unaffected by clinical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 45 publications
9
105
2
Order By: Relevance
“…However, one study did not show any differences (King et al, 2013b). Ethnic differences have been found in the facilitation of temporal summation in patients with OA and hence should be considered as a source of variation (Goodin et al, 2014).…”
Section: Temporal Summationmentioning
confidence: 91%
See 2 more Smart Citations
“…However, one study did not show any differences (King et al, 2013b). Ethnic differences have been found in the facilitation of temporal summation in patients with OA and hence should be considered as a source of variation (Goodin et al, 2014).…”
Section: Temporal Summationmentioning
confidence: 91%
“…Further, it has been found that the CPM is restored in patients after knee replacement where the patients became pain free (Kosek and Ordeberg, 2000;Graven-Nielsen et al, 2012). On the other hand, Finan et al (2013) found no difference in CPM potency between different OA sub-groups and King et al (2013b) found no differences between OA patients and controls.…”
Section: Descending Pain Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Izumi et al, 2016 11 showed the same in severe hip OA patients compared with healthy controls. King et al, 2013 22 found that heat pain threshold and tolerance thresholds were elevated in patients with severe symptomatic KOA but not in patients with less symptomatic KOA compared with healthy controls. Further, studies have found heat related hypoesthesia and hypoalgesia in patients with lateral epicondylalgia 34 increased thermal detection thresholds, and skin biopsies confirmed a loss of small thin cutaneous never fibers.…”
Section: Thermal Testing In Knee Osteoarthritismentioning
confidence: 99%
“…Recently, thermal cutaneous hypoesthesia and hypoalgesia have been reported for knee OA pain 22,23 . A similar loss of function has been seen in patients with, e.g.…”
Section: Introductionmentioning
confidence: 99%